A comparative study of the effect of the oral gavage and the intraperitioneal administration of Cinnamomum camphora on the number of embryos in mice - Syed Gholam Ali Joursarai; sima shahabi; Ali Akbar Moghadamnia; Ebrahim Zabihi; Ghorban Maliji; Tahereh Abbasi; Soghra Ahmadzadeh; Ali-Asghar Younesi; Mohsen Esmaili; Fereshteh Pour Abdolhossein (Babol University of Medical Sciences, 2016)
Background: According to a popular Iranian belief, Camphor can not only suppress libido but also decrease the function of the reproductive system. In this regard, this study was conducted to evaluate the role of Camphor in the number of embryos in mice. Methods: In this study, 40 male and 80 female albino mice, weighing 30-35 g, were randomly divided into 8 groups, including a control group, a sham group that received the vehicle only (olive oil), and six experimental groups that received Camphor. Three experimental groups received camphor by p.o. (gavage) and the other three experimental groups received camphor by i.p. (intraperitioneal) in doses of 10, 20, and 40 mg/kg for 15 days. Mating was confirmed after coupling a male with a female mouse. Vaginal plaque was also considered for mating. Embryos were examined during the period of gestation. Results: The mean number of embryos in control, sham, and received Camphor (10, 20, and 40 mg/Kg) by o. p. were 9.7 ± 4.6, 7.3 ± 4.3, 9.9 ±4.7, 8.6 ± 5.2, and 8.3 ±4.8, respectively. The mean number of embryo in received Camphor (10, 20, and 40 mg/Kg) by i. p. were 7.6 ± 5.4, 8.3 ± 3.4, and 7.3 ± 6.2, respectively. There were no significant differences in the number of embryos between control, sham, and experimental groups in both groups. Conclusion: Further investigations with more focus on the effect of Camphor on sexual behavior in mice need to be carried out.